Assessing Second Language Pragmatics
XV, 366 p.
Keywords: The first book-length collection of studies on the assessment of pragmatic competencies in a second or foreign language. Grounded in theoretical perspectives on communicative and interactional competencies, it examines the reception and production of speech acts through a variety of assessment methods and quantitative and qualitative analyses.